Preparation, Thermal Properties and Decomposition Course of Highly Resistant Potato Starch Graft Poly(Cinnamyl Methacrylate) Materials - Marta Worzakowska (Molecules)
The properties of starch graft poly(cinnamyl methacrylate) copolymers were presented. The “grafting from” method and different ratios of starch to methacrylic monomer were used. The copolymers with the maximum grafting percent (G: 55.3% ± 0.4) using a ratio of starch to methacrylic monomer of 1:3 were obtained. The heterogeneous, non-porous structure materials were prepared. They were characterized by significant lower swelling in polar solvents and moisture absorption but higher swelling in non-polar solvents compared to unmodified potato starch. The chemical resistance in acidic, alkaline and neutral environments for all the tested copolymers was significantly higher compared to the chemical resistance of potato starch. The tested copolymers decomposed in at least three main stages in inert conditions and in at least four main stages in oxidative conditions. Their pyrolysis with the emission of the mixture of volatiles such as aldehyde, acid, ester, alcohol, aromatic, alkene, alkane, H2O, CO2 and CO based on the TG/FTIR studies was proved. The oxidative decomposition included pyrolysis processes combined with oxidation and combustion reactions of volatiles and the formed residues. As a result, the emission of the unsaturated and saturated compounds with carbonyl, hydroxyl, carboxyl and/or ester groups, alkane, alkene, aromatics and its oxidized forms, H2O, CO2 and CO, was observed.